ORGANIZATIONAL CULTURE TRANSFORMATION THROUGH BUSINESS SUCCESS-ORIENTED HR MANAGEMENT PRACTICES - Kurniawansyah Kurniawansyah; Maulidza Nur Fauzi; Zahara Tussoleha Rony; Abdurrahman Sadikin; Ismawati Ismawati (Jurnal Ekonomi, 2023)
The process of transforming organizational culture is a crucial endeavor in order to attain success and enhance competitiveness within the commercial realm. A robust corporate culture that prioritizes commercial success fosters a highly productive, innovative, and adaptable environment. The problem at hand is of significant importance due to the imperative nature of human resource management's role in facilitating cultural transformation. The objective of this study is to examine human resource management strategies that aim to enhance employee competence, performance, and engagement, with the ultimate goal of fostering a collaborative culture and promoting shared responsibility. This study employs the literature review methodology to explore the interconnections between organizational culture reform, human resource management, and business performance. The findings of the study indicate that the initiation of organizational culture transformation necessitates an understanding of the influence of organizational culture on the formation of organizational identity. Consequently, there exists a body of research exploring the impact of HR management on employee development, reward systems, and empowerment within the context of organizational culture transformation strategies. These studies provide valuable insights for the implementation of HR management practices that are aligned with the achievement of business objectives.